Seroepidemiological analysis of toxoplasmosis in college students - Rodrigues, Jaqueline Polizeli; Frei, Fernando; Navarro, Italmar Teodorico; Silva, Luciana Pereira; Marcelino, Monica Yonashiro; Andrade-Junior, Heitor Franco de; Faria, Carolina Arruda de; Santos, Marislene; Ribeiro-Paes, João Tadeu (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2015)
Background Toxoplasmosis is a zoonosis caused by an obligate intracellular parasite, Toxoplasma gondii, which affects warm-blooded animals including humans. Its prevalence rates usually vary in different regions of the planet. Methods In this study, an analysis of the seroprevalence of toxoplasmosis among Brazilian students was proposed by means of IgG specific antibodies detection. The presence of anti-Toxoplasma gondiiantibodies by indirect fluorescent antibody test (IFAT) was also evaluated in order to compare it with enzyme-linked immunosorbent assay (ELISA) and to assess the use of 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) and o-phenylenediamine dihydrochloride chromogens. Results The IFAT method showed a seroprevalence of 22.3%. These results were similar to those obtained by ELISA (24.1%). The seroprevalence was directly estimated from the IgG avidity, which showed that in a sample of 112 students, three of them had acute infection, an incidence of 1.6% in the studied population. Conclusion In this study, the use of different chromogenic substrates in immunoenzymatic ELISA assays did not display different sensitivity in the detection of T. gondii-reagent serum. The extrapolation of results to this population must be carefully considered, since the investigation was conducted on a reduced sample. However, it allows us to emphasize the importance of careful and well prepared studies to identify risk factors for toxoplasmosis, to adopt preventive measures and to offer guidance to at-risk populations about the disease.
Keywords: Toxoplasma gondii; Toxoplasmosis; Enzyme-linked immunosorbent assay; Indirect fluorescent antibody test; Seroprevalence; Epidemiology